Próba oceny skuteczności polityki pieniężnej w Polsce - Noga, Marian (Attempt of assessment of effective monetary policy in Poland, 2006)
The aim of this paper is to present monetary policy making and to attempt an assessment of effective monetary policy in Poland. The author discusses strategy of Direct Inflation Targeting (DIT) by National Bank of Poland (NBP) and its instruments ruled by Monetary Policy Council (MPC). In the final part of the paper the author assesses the influence of external and internal factors on level of inflation in Poland between 2004 and 2006.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 123-131